2007
DOI: 10.1371/journal.pone.0000555
|View full text |Cite
|
Sign up to set email alerts
|

Assortative Mating between European Corn Borer Pheromone Races: Beyond Assortative Meeting

Abstract: BackgroundSex pheromone communication systems may be a major force driving moth speciation by causing behavioral reproductive isolation via assortative meeting of conspecific individuals. The ‘E’ and ‘Z’ pheromone races of the European corn borer (ECB) are a textbook example in this respect. ‘Z’ females produce and ‘Z’ males preferentially respond to a ‘Z’ pheromone blend, while the ‘E’ race communicates via an ‘E’ blend. Both races do not freely hybridize in nature and their populations are genetically differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 65 publications
4
46
2
Order By: Relevance
“…This study demonstrated that a mating barrier exists between the ABB and ECB based on quantitative genetics and comparative analysis between intra-and inter-specific mating trials. Yet, by contrast with the comparative analysis based on multiple crosses in the study by Pélozuelo et al (2007), the present phenotype measurements do not distinguish between the reproductive isolation between the ABB and ECB, and other intrinsic individual propensities Mapping reproductive isolation in Ostrinia spp R Streiff et al to mate. We thus distinguish the mating isolation (mi) trait measured here from the Am trait observed in the study of Pélozuelo et al (2007).…”
Section: Mating Assessmentcontrasting
confidence: 90%
See 4 more Smart Citations
“…This study demonstrated that a mating barrier exists between the ABB and ECB based on quantitative genetics and comparative analysis between intra-and inter-specific mating trials. Yet, by contrast with the comparative analysis based on multiple crosses in the study by Pélozuelo et al (2007), the present phenotype measurements do not distinguish between the reproductive isolation between the ABB and ECB, and other intrinsic individual propensities Mapping reproductive isolation in Ostrinia spp R Streiff et al to mate. We thus distinguish the mating isolation (mi) trait measured here from the Am trait observed in the study of Pélozuelo et al (2007).…”
Section: Mating Assessmentcontrasting
confidence: 90%
“…It thus mainly target the 'Am' (assortative mating) trait described by Pélozuelo et al (2007). This study demonstrated that a mating barrier exists between the ABB and ECB based on quantitative genetics and comparative analysis between intra-and inter-specific mating trials.…”
Section: Mating Assessmentmentioning
confidence: 82%
See 3 more Smart Citations